IMPLEMENTASI FRAMEWORK NODE.JS PADA SISTEM INFORMASI KESEHATAN IBU HAMIL DI KOTA BATAM - Jeni, Jeni Chrisna Sitanggang; Elisa, Erlin (LPPM Universitas Putera Batam, 2024)
The world of technology is developing rapidly, which greatly influences humans to use the convenience provided by the use of technological facilities. In the context of health services, information systems function as the center of health development and are responsible for encouraging, providing, and delivering services. Pregnancy that lasts 9 months requires many examinations to determine the health of the fetus. However, consultations with doctors are sometimes lacking in conveying accurate and precise information due to the large number of patients. Not infrequently, predetermined schedules are often postponed or cancelled. Therefore the aim of this research is To design a Health Information System for Pregnant Women in Batam City using Unified Modeling Language (UML). With the Agile method and using JavaScript and Node.Js